STRATEGIC PLANNING AT THE ENTERPRISE: APPLICATION OF A METHOD OF THE ANALYSIS OF HIERARCHIES FOR THE STRATEGIC ACTIVITY MONITORING - Ilya V. Samarin; Alexander N. Fomin (Статистика и экономика, 2016)
The technique of application of a method of the analysis of hierarchiesfor the solution of problems of monitoring of activity of the enterprise onadvance to a strategic objective in the course of implementation of thecurrent medium-term plan is presented. Problems of an assessment of astate and situation forecasting to the termination of the current planningperiod are considered. The matrix method which is the return method ofthe analysis of hierarchies, allowing to estimate and predict a situationwith implementation of the plan in all structures of the enterprise andrealizing procedure of strategic monitoring at the enterprise is developed. Statistical and analytical methods of the solution of a problemof forecasting are presented. For the solution of a task the statisticalmethod developed algorithm of the numerical solution of a task and itsﬂowchart is submitted. An algorithm for solving the problem of determination of the integral strategic risk the implementation of the set ofevents. Shows an example of solving the problem of determination ofthe degree of achievement of the intermediate objectives for the knownvalues of the degree of implementation of all stipulated by a plan ofactions (works) for the six-level hierarchical scheme.